Frequency of Anxiety and Depression Among Medical Students During Viva Exam: Anxiety and Depression among Medical Students - Ashar Rafi, Muhammad; Shahzadi, Namal; Imtiaz, Iqra; Fatima, Mahnoor; Batool, Masooda; Gul, Seema; Naeem, Aamer (Pakistan Journal of Health Sciences, 2023)
Examinations are an integral part of medical school education and negative emotional states affect the memory, recalling and timely response of the students during the examination. Objective: To find out the frequency of anxiety and depression among medical students at the time of taking the viva examination. Methods: A cross-sectional study was conducted on medical students at the Department of Rehabilitation Sciences, Shifa Tameer-e-Millat University Islamabad, Pakistan. For data collection, Beck Anxiety Inventory and Beck Depression Inventory questionnaires were used. A total of 207 participants were included via inclusion criteria. Inclusion criteria were medical students of age 18-25 years, both males and females having viva examination at the time of data collection. Those students who were already diagnosed with psychological issues were excluded from the study. For the analysis of data SPSS version 21.0 was used. Results: 207 students participated in this research. The majority of the students 115 (56.6%) have mild anxiety levels whereas 103 (49.8%) students were having normal ups and downs that were not considered as depression. 45 (21.7%) students have mild mood disturbance. Conclusions: This study concluded that medical students face a mild level of anxiety and mood disturbance during viva exams